2018
DOI: 10.1515/ceej-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Financialization in the Regional Aspect. An Attempt to Measure a Phenomenon.

Abstract: The aim of the work was to analyze the possibilities of measuring the phenomenon of financialization on a regional basis. The article attempts the move with the measurement of financialization from the level of countries to the level of regions. In the paper, some variables that can measure financialization at the level of voivodeships were used to create an index of regional financialization. The research proposal was verified empirically, using data from 2005–2015 for 16 Polish voivodeships. The results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As a result of the analysis, it may not be unequivocally concluded that the current loan and guarantee funds have a significant impact on the condition of the region. This is certainly due to the region of operation, the scale of their impact and their activity, which is much smaller than that of bank lending campaign (Gemzik-Salwach, and Perz, 2018). Other elements matter as well, such as the amount of capital and the condition, willingness of enterprises to invest.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the analysis, it may not be unequivocally concluded that the current loan and guarantee funds have a significant impact on the condition of the region. This is certainly due to the region of operation, the scale of their impact and their activity, which is much smaller than that of bank lending campaign (Gemzik-Salwach, and Perz, 2018). Other elements matter as well, such as the amount of capital and the condition, willingness of enterprises to invest.…”
Section: Discussionmentioning
confidence: 99%